Effectiveness of Social Media Campaigns to Increase Legislative Voting Intention in Tangerang - Narayana, Ida Bagus Putra; Ria, Desy Nike (Universitas Wiralodra, 2025)
This study analyzes the effectiveness of social media campaign strategies on voters’ voting intention in Tangerang Regency during the 2024 Legislative Election. Social media serves as a vital platform in political communication, enabling political parties and legislative candidates to reach voters more broadly and interactively. The focus of this research is on the campaign strategy of Desy Nike Ria, a legislative candidate from the Perindo Party, candidate number one for the Banten Provincial Parliament (DPRD), representing Tangerang Regency. The study specifically examines the intensity of social media usage, user engagement, and the effectiveness of political messages. This research uses a quantitative approach with primary data collected through a questionnaire distributed to 104 respondents who met the established criteria. The study's scope is limited to the analysis of Desy Nike Ria's campaign and does not cover other factors that may influence voting intention, such as conventional media exposure, economic conditions, or individual voter characteristics. It also does not explore the long-term effects after the election. The results show that the effectiveness of political messages and user engagement on social media significantly influence voting intention. Voters are more likely to be persuaded when campaign messages are clear, engaging, and communicative. Intensity of exposure to political content alone does not have a significant impact, suggesting that message quality is more critical than frequency. These findings offer empirical insight into how digital political communication can shape electoral behavior and provide practical recommendations for candidates and political parties in crafting more effective social media strategies.